Determinant Efficiency Analysis of The National Zakat Board (BAZNAS) Regency/City in West Java - Firmansyah Firmansyah; Aas Nurasyiah; Rida Rosida (Universitas Pendidikan Indonesia, 2020)
This research is intended to determine the factors that influence the efficiency of The National Zakat Board Regency/City in West Java and improve the efficiency level of The National Zakat Board Regency / City in West Java. This research uses Statistical Test Non-Parametric Method Two-Stage Data Envelopment Analysis (DEA) using the production approach and Tobit regression model. Generally, the efficiency level of The National Zakat Board in West Java is relatively good because it achieves a full efficiency value of six National Zakat Board, besides that most of The National Zakat Board in West Java reaches the point of efficiency above average. The factors that cause these inefficiencies are generally less optimal distribution. In the Tobit regression model, from used six variables is the number of employees and Amil, the number of Zakat collector units, the number of payment systems offered, the number of meetings per year, the operational costs, and the total assets, there are only two Variebel values Significant effect on the efficiency of The National Zakat Board, the variable number of meetings and total asset value.